(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
This study takes a novel approach to exploring the changes in inter-organizational relationships in the health insurance industry, which is currently undergoing a digitalisation environment change known as InsurTech. As a unique research method, we constructed a database of the most recent six years of inter-organizational alliances among firms in the health insurance industry and analysed it quantitatively using the social network analysis method. The analysis showed that new entrants, such as IT firms, had expanded their affiliated networks in addition to the traditional primary health insurance industry. First, the network structure tends to be decentralised, and the expanding firms adopt a platform-type network structure.